'The art of surviving': Aaron and Guéra's Scalped as a post-Western. Issue 6 (2nd November 2022) - González, Jesús Ángel
ABSTRACT: The term Post-Western has been used since the 1970s to refer to books and films that are not Westerns but use conventions of the Western genre to analyse contemporary conflicts and issues. The most important contribution to the establishment of this subgenre has been Neil Campbell's monograph Post-Westerns (2013), in which they are described as films coming after and going beyond the traditional Western genre while at the same time engaging with its deeply haunting assumptions and values. This article seeks to adapt the concept of post-Westerns to Comics Studies and focuses on a recent graphic work that can be considered post-Western, Scalped, a 60-issue comic-book series written by Jason Aaron and illustrated by R. M. Guéra, published by Vertigo between 2007 and 2012. It tells a contemporary story of crime, violence and corruption in an Indian Reservation in South Dakota, where the Lakotas live in an environment of utter poverty, drug abuse and hopelessness. Making use of constant flashbacks and different points of view, Scalped makes references to the Western myth and establishes a dialogue with American history and the Western genre to show the contrast with post-Western contemporary nightmares.